+0  
 
+1
109
1
avatar+500 

Suppose $f(x)=\frac{3}{2-x}$. If $g(x)=\frac{1}{f^{-1}(x)}+9$, find $g(3)$.

 May 6, 2021
 #1
avatar+121055 
+2

Let's find  the  inverse.....write

 

y =  1 /  (3 -x)        get x by itself

 

(3-x) y =   1

 

3y - xy  =  1

 

3y   -  1   =   xy

 

(3y - 1)  /  y  =   x         "swap"  x  and  y

 

(3x - 1)  / x  =   y     =  the inverse  

 

So

 

g(x)  =  1/ inverse  +  9  =

 

1 / (3x - 1) / x   + 9  =

 

x /( 3x - 1)    +  9

 

So

 

g(3)  =        3 / ( 3*3 - 1)  + 9     =     (3/8) + 9   =    [ 75] / 9  =    25 / 3

 

 

cool cool cool

 May 6, 2021

36 Online Users